2018
DOI: 10.1111/jpc.14249
|View full text |Cite
|
Sign up to set email alerts
|

Needs of parents in a surgical neonatal intensive care unit

Abstract: Aim While there is evidence of parental needs in the neonatal intensive care unit (NICU), parents of newborns admitted for general surgery are an under‐researched population. This study aimed to identify needs in parents of newborns admitted to the NICU for general surgery and whether health‐care professionals meet these needs. Methods This was a prospective cohort study of 111 parents (57% mothers) of newborns admitted to a surgical NICU for general surgery in Australia from January 2014 to September 2015. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
1
9
1
7
Order By: Relevance
“…The interview results showed that medical information about the children was still the most critical concern of parents under COVID-19. These data were inconsistent with the previous studies (11,12), which revealed that in the regular period, enhanced confidence and reduced anxiety were the primary psychological needs. The underlying cause for this difference may be attributed to telephone communication during the epidemic, which could reduce the sense of intimacy and authenticity compared to face-to-face communication.…”
Section: Disease Informationcontrasting
confidence: 99%
“…The interview results showed that medical information about the children was still the most critical concern of parents under COVID-19. These data were inconsistent with the previous studies (11,12), which revealed that in the regular period, enhanced confidence and reduced anxiety were the primary psychological needs. The underlying cause for this difference may be attributed to telephone communication during the epidemic, which could reduce the sense of intimacy and authenticity compared to face-to-face communication.…”
Section: Disease Informationcontrasting
confidence: 99%
“…Our results are consistent with previous studies that explored parental perceptions of the NICU experiences and found that NICU parents worldwide experienced an emotional rollercoaster [36] and mental health problems [37]. In other countries, the need for comprehensible and honest assurance and information were more important than support and comfort [13,38,39]; however, this qualitative study suggested that empathic concern and warmer, kind and comforting words even when delivering negative news might be preferable for mothers in South Korea. Interestingly, most mothers who gave birth to premature or low-birthweight children tended to call the babies "ireundungi"da Korean word for refined (a premature baby who starts his/her life earlier as a fast starter created by the Dasomi Project, a Korean social enterprise)drather than "misuka"dwhich implies a negative connotation related to social stigma regarding the preterm infant.…”
Section: System-level Challengessupporting
confidence: 91%
“…Research to date has largely focused on identifying parental needs rather than explored ways in which these needs are actually met, or not met, at the NICU [19]. Moreover, the psychosocial needs reported by parents of extremely premature infants at the NICU have not specifically been studied.…”
Section: Introductionmentioning
confidence: 99%